Crises Management Analyses of Iraqi Swimming Federation’s Administrative Bureau - Uday, Baraa; Ali, Suha (Journal of Physical Education, 2021)
The research aimed at identifying the reality of crises management in central administrative bureau in governorates swimming federation from the administrative bureaus’ point of view as well as first class referees. The problem of the research lies in answering whether the central or regional administrative bureaus of Iraqi swimming federation are able to administer crises that they face. The researchers used the descriptive method on 85 member and referee who represent Iraqi central swimming federation as well as regional federation. The subjects were (80) members and referees. A scale was designed for crises administrations that was applied on the subject. The data was collected and treated to come up with the conclusions. The researchers concluded that crises administration reality shows great weakness that leads to increasing the effects of these crises that negatively affected the federation.